STRATEGI DASAR PENGENDALIAN MULTI ROBOT APUNG DAN MANFAATNYA - Tjahjana, Redemtus Heru (MATEMATIKA, 2014)
This paper describes floating multi-robot control strategies. Exposure starts from inspiration and the use of floating multi-robot in daily life, especially in the industrial world. Furthermore, with the model of multi-robot and functional model that describe the state of the cost to be met the floating robots, floating multi-robot control designed with optimal control strategy. The design of optimal control is done through the Pontryagin Maximum Principle, brings the model to a system of equations consisting of state equations and costate equations. In the system of states equations, each having initial and final condition, in the costate equations system has no requirements at all. The next problem is converted to the initial value problem and search for the approximate initial condition equation of state auxiliary systems which has no requirements using a modified method of steepest descent. Thus, the control of multi-robot successfully performed and the simulation results presented on the results and discussion.